THE FEASIBILITY STUDY OF INVESTING IN MODERN DAIRY FARMING: CASE STUDY DAIRY FARMER, SA KAEO PROVINCE - Sukkasam, Naddaporn; Chotkunakitti, Phatnatcha (Journal of MCU Nakhondhat, 2024)
The objective of this research was to 1) Study costs and return from dairy farming and 2) Study problems in dairy farming of dairy farmers in Sakaeo province. This research is a quantitative research. The sample was selected voluntarily. The research samples included 25 dairy farms of dairy farmers in Sakaeo province that were not in the Smart Farm system and 5 dairy farms that have been in the Smart Farm system. Data was analyzed by using descriptive statistics to describe the data, including Mean and Percentage. The results showed that: 1) In term of costs and return on investment in dairy farming for 10 years, modern dairy farming had a total cost of approximately 30 million Baht. Return measured by payback period of modern dairy farming was 3 years, 3 months, and 13 days. The Net Present Value of modern dairy farming was 17,785,387.45 Baht and the Internal Rate of Return of those farms was 19.25 percent, which was higher than the interest rate of commercial banks. In conclusion, investing in a dairy farm is a worthwhile project. 2) Regarding in problems in raising dairy cows for farms both without entering the Smart Farm system and entering the Smart farm system, the problems were high costs of raising, Lack of in-depth knowledge about dairy farming, and lack of tools and equipment. Regarding farms that are not in the Smart farm system, if they want to upgrade into the Smart Farm system, there will be problems of insufficient usable space on the farm. In addition, it requires high capital.